Hubungan Tingkat Nyeri LBP dengan ADL pada Lansia di Puskesmas Padang Kandis - Natasya Alamanda Martias; Roza Mulyana; Yuliarni Syafrita (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
As the elderly age, there are changes in physical changes that affect all systems, including the musculoskletal system. One of the daily health problems that often interfere with Activity of Daily Living in the elderly is low back pain (LBP)./1. This study aims to determine the relationship between LBP pain levels and ADL in elderly women in the Padang Kandis Health Center working area, Lima Puluh Kota Regency. This study is an observational analytic study with a cross sectional approach. The sampling technique used consecutive sampling technique with a total sample of 45 samples. Data collection using the Visual Analogue Scale (VAS) questionnaire, LBP, Katz Basic Activities Of Daily Living Scale (Index Katz). Data analysis using the Pearson Chi-Square test. The results of the Chi-Square test obtained a significant value (p-value) of 0.000 (p < 0.05). The p-value is smaller than 0.05 (0.000 <0.05), so the test decision is Ha accepted, which means “there is a relationship between the level of LBP pain and ADL in the elderly in the Padang Kandis Health Center working area, Guguak District, Lima Puluh Kota Regency, West Sumatra Province”. This study shows that there is a relationship between the level of LBP pain and ADL.